2016
DOI: 10.1055/s-0036-1579549
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Volar Ulnar Rim Fractures of the Distal Radius: Current Techniques and Review of the Literature

Abstract: Background?Distal radius fractures involving the lunate facet can be challenging to manage. Reports have shown the volar carpal subluxation/dislocation that can occur if the facet is not appropriately stabilized. Literature Review?Recent emphasis in the literature has underscored the difficulty in managing this fracture fragment, suggesting standard volar plates may not be able to adequately stabilize the fragment. This article reviews the current literature with a special emphasis on fixation with a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 19 publications
0
38
0
2
Order By: Relevance
“…Nowadays, several fixation options have been described for volarlly unstable distal radius fractures with a small VLF to prevent loss of reduction after operative fixation, and they include a distally placed volar locking plate, a volar rim plate, fragment-specific fixation (wire form or hook plate), or the use of supplemental fixation methods such as sutures, pinning, or external fixation [4,[7][8][9][10][11][12][13][14][15][16][17][18]. These alternative fixation methods such as a distally placed volar locking plate, a volar rim plate (A) (B) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, several fixation options have been described for volarlly unstable distal radius fractures with a small VLF to prevent loss of reduction after operative fixation, and they include a distally placed volar locking plate, a volar rim plate, fragment-specific fixation (wire form or hook plate), or the use of supplemental fixation methods such as sutures, pinning, or external fixation [4,[7][8][9][10][11][12][13][14][15][16][17][18]. These alternative fixation methods such as a distally placed volar locking plate, a volar rim plate (A) (B) Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of reduction after operative fixation of volarly unstable distal radius fractures with a volar lunate facet fragment (VLF) is considered problematic because it results in carpal subluxation or dislocation and subsequent impaired function, pain, limitation of range of motion, and posttraumatic arthritis [ 1 , 2 ]. Previous studies have reported that the incidence of failure of fixation is 4–13% [ 2 4 ]. Several factors have been reported to contribute to this.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the choice between palmar and dorsal surgical approaches, there are no standard guidelines. Palmar approach has become more and more popular in adults, 9 , 10 , 11 because it is more beneficial for wrist function recovery than the dorsal approach. 12 For children, the majority of distal radius fractures are caused by falling on their palms with forearm in pronation and wrist in extension position and result in forward-angulated fractures and extension-type fractures.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller dimensions of these implants can facilitate accurate placement to capture a specific fragment, but these are insufficient by themselves, and must be used in conjunction with other implants. Reports have shown satisfactory outcomes, and while tendon irritation was reported with early versions of this plate, 31 more recent reports with lower profile devices have shown these complications to be less prevalent. 32 Chin and Jupiter first described a wire loop fixation technique for treatment of intra-articular fragmentation in distal radius fractures.…”
Section: Fracture Managementmentioning
confidence: 93%